A phylogenetic framework for the North American bumblebee species of the subgenus Bombus sensu stricto (Bombus affinis, B. franklini, B. moderatus, B. occidentalis & B. terricola) based on mitochondrial DNA markers. (Hymenoptera: Apidae: Bombus). - Bertsch, Andreas; Hrabé de Angelis, Martin; Przemeck, Gerhard K. H. (Contributions to Entomology = Beiträge zur Entomologie, 2010)
Queens of Bombus affinis, B. moderatus, B. occidentalis and B. terricola were collected from different localities throughout North America. In addition, males of B. franklini, B. occidentalis and B. terricola were collected. Mitochondrial cytochrome oxidase subunit I (COI) was sequenced from 24 specimens (Partial sequences length 1005 bp). Interspecific sequence divergence was about 30–50 base substitutions and approximately 0.05–0.13 in Tamura-Nei genetic distance, whereas the intraspecific sequence divergence was only 1–2 base substitutions and about 0.001–0.002 in Tamura-Nei genetic distance. Because there are no gaps in the alignments of the COI sequences, single nucleotide sites can be used as positional homologies. Each taxon is characterised by about 8 to 20 substitutions, which are unique (“private”) and can be used as diagnostic characters to define and identify this taxon. Three clusters in the topology of the phylogenetic tree were obtained: B. moderatus, which is con-specific to the East Asian B. albocinctus, a species pair B. affinis – B. franklini somehow related to the Eurasian B. lucorum and a species pair B. terricola – B. occidentalis without obvious connection to any Old World species.